DevOps - Ebert, Christof; Gallardo, Gorka; Hernantes, Josune; Serrano, Nicolas (IEEE software, 2016)
Building on lean and agile practices, DevOps means end-to-end automation in software development and delivery. Hardly anybody will be able to approach it with a cookbook-style approach, but most developers will benefit from better connecting the previously isolated silos of development and operations. Many DevOps tools exist that can help them do this.